A comparative kinetic and mechanistic study between tetrahydrozoline and naphazoline toward photogenerated reactive oxygen species - Criado, Susana Noemi (2010)
Kinetic and mechanistic aspects of the vitamin B2 (riboflavin [Rf])-sensitized photo-oxidation of the imidazoline derivates (IDs) naphazoline (NPZ) and tetrahydrozoline (THZ) were investigated in aqueous solution. The process appears as important on biomedical grounds, considering that the vitamin is endogenously present in humans, and IDs are active components of ocular medicaments of topical application. Under aerobic visible light irradiation, a complex picture of competitive interactions between sensitizer, substrates and dissolved oxygen takes place: the singlet and triplet (3Rf*) excited states of Rf are quenched by the IDs: with IDs concentrations ca. 5.0 mm and 0.02 mm Rf, 3Rf* is quenched by IDs, in a competitive fashion with dissolved ground state oxygen. Additionally, the reactive oxygen species: O2(1Δg), O2 •-, HO• and H2O2, generated from 3Rf* and Rf•-, were detected with the employment of time-resolved methods or specific scavengers. Oxygen uptake experiments indicate that, for NPZ, only H2O2 was involved in the photo-oxidation. In the case of THZ, O2 •-, HO• and H2O2 were detected, whereas only HO• was unambiguously identified as THZ oxidative agents. Upon direct UV light irradiation NPZ and THZ generate O 2(1Δg.), with quantum yields of 0.2 (literature value, employed as a reference) and 0.08, respectively, in acetonitrile.